2019
DOI: 10.18415/ijmmu.v6i5.1095
|View full text |Cite
|
Sign up to set email alerts
|

The Notary Authority in Resolving Land Disputes with Deed of Peace

Abstract: Disputes that often occur are usually related to ownership of land, this is because of the important role of land in human life, so that land becomes an object that is prone to disputes or disputes between people, this occurs because human needs for land are increasing, but the land supply is relatively fixed. Notary as a public official trusted by the community to resolve land disputes through a peace deed made by a notary to ensure legality. The method used is empirical juridical research. Research data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the implementation of Cyber Notary is certainly possible by making changes to the relevant legal regulations and the development of supporting infrastructure and adequate electronic systems. Meanwhile, the study conducted by Putri et al (2019) about the authority of a notary public in resolving land disputes with a deed of peace, showed that 1) Notary was authorized to make a peace deed to guarantee legal certainty for the parties to settle land disputes in accordance with article 15 Paragraph (2) letter f of the UUJN and 2) The peace deed drawn up by a Notary Public is an Authentic Deed but not final binding like a van dading deed decided from the results of mediation in court. In addition, another similar study has been conducted by Pratiwi et al (2019) about 'Authority and Position of Notary Deed in the Land Sector'.…”
Section: Introductionmentioning
confidence: 99%
“…However, the implementation of Cyber Notary is certainly possible by making changes to the relevant legal regulations and the development of supporting infrastructure and adequate electronic systems. Meanwhile, the study conducted by Putri et al (2019) about the authority of a notary public in resolving land disputes with a deed of peace, showed that 1) Notary was authorized to make a peace deed to guarantee legal certainty for the parties to settle land disputes in accordance with article 15 Paragraph (2) letter f of the UUJN and 2) The peace deed drawn up by a Notary Public is an Authentic Deed but not final binding like a van dading deed decided from the results of mediation in court. In addition, another similar study has been conducted by Pratiwi et al (2019) about 'Authority and Position of Notary Deed in the Land Sector'.…”
Section: Introductionmentioning
confidence: 99%